The microstructure and mechanical properties features of laser welded joints of low-carbon tubular steel; Welding International; Vol. 34, iss. 1-2 - Derevyagina L. S. Lyudmila Sergeevna; Gordienko A. I. Antonina Ildarovna; Malikov A. G.; Orishich A. M. Anatoliy; Kashiro P. O. (2020, 2020)
Title screen